Time-of-flight secondary ion mass spectrometer: a novel tool for lipid imaging. (August 2011) - Ayciriex, Sophie; Touboul, David; Brunelle, Alain; Laprévote, Olivier
Mass spectrometry imaging is becoming an important complementary alternative technique to more well-established imaging techniques. It can determine the spatial distribution of a large number of intact molecular or fragment ions generated directly from tissue sections or single cells. Secondary ion mass spectrometry coupled with a time-of-flight mass spectrometer imaging technique, using a cluster ion beam as primary bombardment particles, is now an analytical tool of reference for high lateral resolution imaging (1–2 µm) of biological surfaces. It exhibits a high efficiency for lipids and inorganic species. While numerous studies have been performed with cells in culture or with animal models, few clinical studies dedicated to lipid perturbations have been performed, to date. This article will compare the main advantages of time-of-flight mass spectrometry imaging over other mass spectrometry imaging methods and several biological applications will be detailed.